Metaphysical Newton - Simões, Eduardo (Argumentos - Revista de Filosofia, 2015)
The aim of this paper is to present the thought of Isaac Newton beyond the boundaries of experimental physics. It is an effort in, even knowing the genius of the English scientist objectivity, demonstrate that his theory escapes the field of physics to metaphysics when entering into its gravitational theory unprovable elements, such as absolute space, absolute time, ether, etc. The Newton’s behavior reflects a common practice to scientific theories that, even without explicit admission of Science, compared to the absence of the material counterpart of the theory, introduces ad hoc elements, whose function is to maintain the formal and universal identity system.